1978
DOI: 10.1038/bjc.1978.217
|View full text |Cite
|
Sign up to set email alerts
|

Restricted autologous lymphocytotoxicity in lung neoplasia

Abstract: Summary.-Blood lymphocytes from 47 patients with lung carcinoma have been tested for cytotoxicity against cells isolated from the autologous tumour. Significant cytotoxic potential was found in 15 cases. The effectors were also tested against allogeneic tumour targets from lung and other sites. Reactions were only rarely detected (2/32 positive against lung and 1/13 positive against non-lung cells). The restriction of cytotoxicity to the autologous combination was also apparent in in vitro-generated effectors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 19 publications
(21 reference statements)
2
16
0
Order By: Relevance
“…The effects were usually weak. The reactivity was exerted by the T cell-enriched subset and mainly autologous tumor cells were affected (29,18). Although not proven, we may consider the in vitro cytotoxicity as a manifestation of antitumor autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…The effects were usually weak. The reactivity was exerted by the T cell-enriched subset and mainly autologous tumor cells were affected (29,18). Although not proven, we may consider the in vitro cytotoxicity as a manifestation of antitumor autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of stimulation PBL and TAL from ovarian cancer patients showed no evidence of appreciable cytotoxicity against autologous targets Figure 3), whereas -30% of subjects with other human tumours have PBL cytotoxic against autologous neoplastic cells (Vose et al, 1977a(Vose et al, , 1978Zarling et al, 1979). However when lung cancer was considered by histological subtype, evidence for autologous recognition was confined to squamous cell carcinoma and to adenocarcinoma (Vose et al, 1978). Our previous findings with ovarian carcinoma were confirmed in the limited series of subjects considered in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh tumour cells from human neoplastic tissues are generally resistant to natural cytotoxicity as measured by conventional cytolysis assays (Pattengale et al, 1982;Serrate et al, 1982;Vanky et al, 1980;Verkmeister et al, 1979;Vose et al, 1977aVose et al, , 1977bVose et al, , 1978Vose & Moore, 1980;Zarling et al, 1979). In a study with various human tumours, mainly of mesenchymal origin, Vanky et al reported that IFN-induced killing of fresh biopsy cells only if allogeneic combinations of PBL and target cells were used (Vanky et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have attempted in vitro generation of tumor-specific cytotoxic lymphocytes. 1,2) Vose et al 3) and Vanky et al 4,5) have succeeded in the induction of autologous tumor-specific cytotoxic lymphocytes by using mixed cultures of peripheral blood mononuclear cells (PBMC) with untreated autologous tumor cells. Grimm et al 6) and Lotze et al 7) have shown that lymphokine-activated killer (LAK) cells are induced by culturing PBMC in interleukin-2 (IL-2)-containing medium.…”
mentioning
confidence: 99%